Cross‐talk Between Host, Microbiome and Probiotics: A Systems Biology Approach for Analyzing the Effects of Probiotic Enterococcus faecium NCIMB 10415 in Piglets. Issue 3 (12th February 2014) - Twardziok, S. O.; Pieper, R.; Aschenbach, J. R.; Bednorz, C.; Brockmann, G. A.; Fromm, M.; Klingspor, S.; Kreuzer, S.; Lodemann, U.; Martens, H.; Martin, L.; Richter, J. F.; et al.
Abstract A comprehensive data‐set from a multidisciplinary feeding experiment with the probiotic Enterococcus faecium was analyzed to elucidate effects of the probiotic on growing piglets. Sixty‐two piglets were randomly assigned to a control (no probiotic treatment) and a treatment group (E. faecium supplementation). Piglets were weaned at 26 d. Age‐matched piglets were sacrificed for the collection of tissue samples at 12, 26, 34 and 54 d. In addition to zootechnical data, the composition and activity of intestinal microbiota, immune cell types, and intestinal responses were determined. Our systems analysis revealed clear effects on several measured variables in 26 and 34 days old animals, while response patterns varied between piglets from different age groups. Correlation analyses identified reduced associations between intestinal microbial communities and immune system reactions in the probiotic group. In conclusion, the developed model is useful for comparative analyses to unravel systems effects of dietary components and their time resolution. The model identified that effects of E. faecium supplementation most prominently affected the interplay between intestinal microbiota and the intestinal immune system. These effects, as well as effects in other subsystems, clustered around weaning, which is the age where piglets are most prone to diarrhea.